Small Eco Houses : Living Green in Style. - Paredes Benítez, Cristina, ....-; Sànchez Vidiella, Alex, ....- (Barcelona : Universe Publishing, 2011)
Fresh perspectives on how good design can create stylish yet ecologically sound living spaces in small-scale homes. Anyone who has faced the challenges of limited living space will find inspiration in this survey of the latest trends in environmentally sensitive, small-scale residential designs. More than fifty residential spaces are profiled-from woodsy houses and repurposed barns to cool apartments and urban lofts-both inside and out. Most of the projects were designed by up-and-coming architects, and each design proves that small-scale efficiency as well as beautiful, thoughtful design can overcome the apparent constraints of a small setting. Environmental impact is a growing concern, so each project was chosen because of its ecological sensitivity. Each case history describes the challenges confronting the designer and the solutions. Creating color schemes to enhance the feeling of openness, taking advantage of high ceilings to make multiple levels, and using collapsible furniture and sliding doors to maximize space are some of the design solutions that can be applied in any situation. Filled with beautiful color photographs and helpful floorplans, this book is a remarkable showcase of how good design can transform any small space into a comfortable, modern-and environmentally sensitive-home.
Keywords: Architectuur; Duurzaam bouwen; Ecologisch bouwen